Silica-Rice Husk as Adsorbent of Cr (VI) Ions Prepared through Sol-Gel Method - Siti Rodiah; Mifta Huljana; Jauharuddin Luthfi Al Jabbar; Chairul Ichsan; Hasan Marzuki (Walisongo Journal of Chemistry, 2021)
One of the heavy metals contained in the textile industry wastewater is chromium (Cr). Chromium hexavalent ions (Cr6+) are highly toxic and its accumulation in the human body will cause various negative impacts. This study aimed to determine the characteristics of silica synthesized by the sol-gel method to gain homogeneity and high purity. Synthesized silica was calcined at 700°C for 4 hours and its performance to adsorb Cr(VI) ions  in textile wastewater was investigated. The presence of -OH group from silanol (–Si-OH) was appeared at wavenumber 3367.70 cm-1, meanwhile siloxane functional groups were recorded at 1056.99 cm-1 and 784.38 cm-1 due to the O-Si-O asymmetric stretching and Si-O bending vibration. Optimum conditions of silica to adsorb Cr(VI) ions took place at pH 2 and contact time of 90 minutes by adsorption efficiency of 75,65% and followed the Freundlich isotherm.